Facultative endosymbionts mediate dietary breadth in a polyphagous herbivore. (18th May 2015) - Wagner, Steven M.; Martinez, Adam J.; Ruan, Yong‐Ming; Kim, Kyungsun L.; Lenhart, Paul A.; Dehnel, Allison C.; Oliver, Kerry M.; White, Jennifer A.
Summary: Intraspecific variation in dietary breadth can influence important ecological and evolutionary processes, yet the mechanisms generating this variation are usually unknown. Maternally transmitted bacterial symbionts frequently infect insect herbivores, and many have been shown to mediate key ecological interactions. For polyphagous herbivores, infection with particular symbionts is often strongly correlated with feeding on particular plant species, suggesting that facultative symbionts might directly determine herbivore food plant specificity. However, previous tests of this hypothesis have returned inconsistent results, providing little empirical support for a causal relationship between facultative symbiont infection and dietary breadth. Here, we investigate whether heritable facultative symbionts mediate dietary breadth in the polyphagous aphid, Aphis craccivora . We first determined that asexual clones of the aphid differ dramatically in performance across two leguminous food plants, locust and alfalfa, and could be considered biotypes with distinct ecological characteristics. The heritable symbiont Arsenophonus is strongly associated with locust‐origin aphids. We created experimental lines that share aphid genotypes but differed with respect to Arsenophonus infection status, and compared performance across three food plant species. Naturally Arsenophonus‐ infected clones performed 2–4× better on locust and up to 75% worse on two alternate plant species than uninfected controls, clearly demonstrating that Arsenophonus promotes specialization on locust. In both laboratory and field experiments, uninfected locust‐ and alfalfa‐origin clones exhibited similar and modest performance on locust, indicating that the 'locust‐associated biotype' would not exist without Arsenophonus . We also hypothesized that moving Arsenophonus, via transinfection, to an alfalfa‐origin lineage would improve performance on locust and serve to expand dietary breadth. Indeed, transinfection doubled aphid performance on locust and halved aphid performance on alfalfa. However, because this aphid lineage naturally performs better on alfalfa, the transinfected symbiont functionally equalized aphid performance between locust and alfalfa, making the alfalfa biotype more generalized. Thus, the same symbiont can either reduce or expand dietary breadth, depending on host genotype. Our results unequivocally demonstrate that symbiont gain or loss can instantaneously and substantially change the topology of food plant use in a polyphagous insect, modifying diet in ways that potentially influence the insect's ecological niche, evolutionary trajectory and pest status. Abstract : Lay Summary